Confirmation Bias and Investment Decisions - Nur Afifah Hindriyani Astuti; Axel Giovanni; Siti Marwiyah; Dina Budiani; Yuniar Fitri Anggraeni; Athfin Ghani Wibawa (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study aims to analyze the extent of development regarding research on the relationship between confirmation bias and investment decisions based on google scholar data base using bibliometric analysis, so as to see further research opportunities. The method used in this research is descriptive bibliometric analysis. There are 500 articles from the search results through Publish or Perish indexed by Google Scholar in 2000-2020 which are then stored in RIS format and processed through VOSviewer. The results of the co-authorship analysis show that Mikalef, P., Barber, B.M., and Grili, L. have the highest publication rate on this topic, both producing 5 documents. In addition, this analysis also shows a relationship that is divided into 3 clusters. While the results of co-occurrence analysis show that there are 8 clusters based on terms that become keywords in the article. Based on the results of bibliometric analysis, the topic of investment and confirmation bias has the brightest color than other keywords. This indicates that the topic has been widely used. Then based on overlay visualization on co-occurrence, the topic of investment and confirmation bias has a blue color. This indicates that research on these topics was widely conducted from 2000 to 2010. The keywords investment and confirmation bias have the brightest color than other keywords. This shows that many of the 500 articles analyzed through VosViewer have used these keywords.